Peroxisome Proliferator-Activated Receptor (PPAR)γ can inhibit chronic renal allograft damage - Kiss, Eva; Popovic, Zoran V.; Bedke, Jens; Adams, Judith; Bonrouhi, Mahnaz; Babelova, Andrea; Schmidt, Claudia; Edenhofer, Frank; Zschiedrich, Inka C.; Domhan, Sophie; Abdollahi, Amir; Schäfer, Liliana; et al. (The American journal of pathology, 2010)
Chronic inflammation and fibrosis are the leading causes of chronic allograft failure. The nuclear receptor peroxisome proliferator-activated receptor (PPAR)γ is a transcription factor known to have antidiabetogenic and immune effects, and PPARγ forms obligate heterodimers with the retinoid X receptor (RXR). We have reported that a retinoic acid (RAR)/RXR-agonist can potently influence the course of renal chronic allograft dysfunction.
Gesehen am 14.03.2023